The Alaska Sanders affair : a novel - Dicker, Joël, 1985- (HarperVia, an imprint of HarperCollins Publishers, 2024)
April 1999. The body of Alaska Sanders is found on the shore of a lake near the quiet town of Mount Pleasant, New Hampshire. The young woman's death rocks the small community, but the murder is quickly solved. Within days, two suspects were identified. One died, the other pleaded guilty. Case closed. But, eleven years later, the death of another woman in a fast-food parking lot changes everything. Marcus Goldman, celebrity author and amateur investigator, picks up a thread that will unravel not only an open and shut case, but the very fabric of his best friend's life. Sergeant Perry Gahalowood, who led the original investigation, is hell-bent on setting the record straight. Teaming up with Marcus, he seeks redemption in most the intricate and testing case of his career.